Publication manual of the American Psychological Association - American Psychological Association (USA) (Washington D.C. American Psychological Association, 2002)
The Publication Manual of the American Psychological Association is the style manual of choice for writers, editors, students, and educators in the social and behavioral sciences. It provides invaluable guidance on all aspects of the writing process, from the ethics of authorship to the word choice that best reduces bias in language. Well-known for its authoritative and easy-to-use reference and citation system, the Publication Manual also offers guidance on choosing the headings, tables, figures, and tone that will result in strong, simple, and elegant scientific communication.